Low Frequency Noise and Its Assessment and Evaluation - Stanislav ZIARAN (Archives of Acoustics)
The main aim of this paper is to present recent knowledge about the assessment and evaluation of low frequency noise and infrasound close to the threshold of hearing and the potential effects on human health. Low frequency noise generated by air flowing over a moving car with the open window is chosen as a source of noise. The noise within the interior of the car and its effects on a driver’s comfort at different velocities is analyzed. An open window at high velocity behaves as a source of specifically strong tonal low frequency noise which is annoying. The interior noise of a passenger car was measured under different conditions; while driving on normal highway and roadways. First, an octave-band analysis was used to assess the noise level and its impact on the driver’s comfort. Second, a Fast Fourier Transform (FFT) analysis was used for the detection of tonal low frequency noise. Finally, the paper suggests possibilities for scientifically assessing and evaluating low frequency noise but not only for the presented source of the sound.